(untitled) (Medical Forum Monthly, 2023)
Objective: To assess diagnostic accuracy of thrombocytopenia and Fib 4 Score in predicting esophageal varices using endoscopy as gold standard among patients with chronic liver disease. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at the Study was conducted at advanced GI & Liver Tower, hospital, Multan, from 15-09–2022 to 15-06-2023. Methods: A total of 377 patients with chronic liver disease aged between 20-60 years were included. Three ml of venous blood sample was drawn and sent to the Central laboratory of the hospital for platelet count and other biochemical tests. The FIB-4 score was calculated for all patients and endoscopy was carried out for all enrolled patients to visualize esophageal varices. Results: Mean age of these patients with CLD was 46.20±7.80 years (range; 33 years to 60 years) and 232 (61.5%) were male patients. Grade 1 esophageal varices were noted in 67 (17.8%), grade 2 in 181 (48.0%), grade 3 in 40 (10.6%). Sensitivity of thrombocytopenia was 38.89%, Specificity was 75.53%, PPV was 84.85%, NPV was 28.16% and Diagnostic Accuracy was 48.01%. For FIB score >3, Sensitivity was 34.03%, Specificity was 78.65%, PPV was 83.76%, NPV was 26.92% and Diagnostic Accuracy was 44.56%. Conclusion: Thrombocytopenia and FIB score >3 revealed good diagnostic accuracy in predicting esophageal varices in CLD patients. These are simple tests which can be easily employed by treating physicians to anticipate disease severity in these patients.